The Influence of Indonesian Language Learning Methods Viewed from the Aspect of Learning Media Usage Class X Students of SMK Pratidina Makassar - Saleh. S, Muh. (Jurnal Ar Ro'is Mandalika (Armada), 2025)
This study aims to find effective learning solutions and solve problems by developing teaching methods that are used to achieve meaningful learning objectives. The selection of teaching methods is a procedure, sequence, steps, and approach used by educators in designing the achievement of learning goals. The selection of methods and the use of Indonesian language learning models, such as the grammar-translation method, the direct method, and the audiolingual method, demonstrate a dominant characteristic. The use of Indonesian language teaching methods is a "theory" of Indonesian language instruction, which means a practical theory. This study aims to scientifically examine various effective learning methods. The use of methods in learning is one of the key aspects that must be studied and analyzed in Indonesian language teaching. The development of science and technology has led the education system in Indonesia to become influenced by extreme learning models or methods. Consequently, Indonesian language teaching has lacked a systematic reference or body of knowledge (core knowledge) on learning methods for decades. The results of this study show a significant impact with the proper selection of learning methods and the use of learning media, which can lead to the discovery of truth and new knowledge for students. Therefore, the choice of method and the use of learning media must be precise, as many methods are more inclined toward personal opinions (views) rather than facts (reality).